Monetary Policy News and Exchange Rate Responses: Do Only Surprises Matter? - Rasmus Fatum; Barry Scholnick (University of Copenhagen, Economic Policy Research Unit (EPRU), 2005)
This paper shows that exchange rates respond to only the surprise component of an actual US monetary policy change and that failure to disentangle the surprise component from the actual monetary policy change can lead to an underestimation of the impact of monetary policy, or even to a false acceptance of the hypothesis that monetary policy has no impact on exchange rates. This finding implies that there is a need for reexamining the empirical analyses of asset price responses to macro news that do not isolate the unexpected component of news from the expected element. In addition, we add to the debate on how quickly exchange rates respond to news by showing that the exchange rates under study absorb monetary policy surprises within the same day as the news are announced.
Keywords: E52; F31; G14; 330; expectations; monetary policy; federal funds futures; exchange rates; Geldpolitik; Wechselkurs; Ankündigungseffekt; USA